Oxidative Stress Assessment in Colorectal Cancer Patients: Erbil Population Study - Qadir, Vyan A.; Abdoulrahman, Kamaran K. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
Colorectal cancer (CRC), a global health challenge, exhibits rising incidence in low-income nations due to lifestyle changes. Oxidative stress, indicated by reactive oxygen species imbalance and Malondialdehyde (MDA), is linked to CRC. This study investigates oxidative stress markers, antioxidant enzymes, genetic markers, cellular regulation markers, and Vitamin E in CRC patients in Erbil. Ninety CRC patients and 30 healthy controls provided blood samples, processed and stored at –20°C. Enzyme-linked immunosorbent assay kits quantified oxidative stress, antioxidant markers, and Vitamin E. Oxidative stress markers showed significant differences, with elevated MDA and 8-hydroxy-2’-deoxyguanosine levels in patients. Nitrotyrosine exhibited lower expression in patients. Antioxidant enzymes glutathione peroxidase and superoxide dismutase were enhanced in patients, while glutathione (GSH), glutathione reductase and catalase levels were significantly lower in patients. The genetic marker KRAS showed a substantial decrease in patients (<0.0001) but both adenomatous polyposis coli (APC) and CRC antigen (CCA) were higher. Serum vitamin E levels were significantly lower in patients (71.78 ± 6.368) compared to controls (142.3 ± 4.828, p < 0.0001). Elevated oxidative stress, altered enzymatic activity, significantly lower expression of KRAS, and higher expression of APC and CCA in the patient group. Furthermore, reduced Vitamin E levels were observed in the patient group, highlighting potential challenges in antioxidant defense.